Community Knowledge, Attitude, and Practice toward Self-Medication and It’s Influencing Factor in Central Java: A Cross-Sectional Study - Yulianti, Tri; Fitri Muazizah, Anisa (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2024)
Background: Self-medication refers to people selecting and using medications to treat self-identified diseases or symptoms. Self-medication practices vary between communities and are impacted by a variety of factors. Understanding self-medication knowledge, attitude, and practice is essential to minimize risks and negative consequences.Objectives: This study aims to analyze the community's knowledge, attitude, and practice (KAP) concerning self-medication and the factors that influence it.Methods: A cross-sectional study was undertaken among the general community in Central Java, Indonesia. In this study, 396 participants were recruited and interviewed using a validated Knowledge, Attitudes, and Practices questionnaire focused on self-medication. The sociodemographic variables and levels of knowledge, attitudes, and practices were represented using descriptive statistics in the statistical analysis. Bivariate and multivariable logistic regression analysis tests were employed to determine the relationship between socio-demographic characteristics and levels of knowledge, attitudes, and practices.Results: The results showed that the age group of 36-45 years had the most significant percentage of participation, with 103 individuals. The sample consisted of 235 females, 59.3% of the total participants. Respondents had a sufficient level of knowledge (39.6%), good attitudes (51.8%), and good practice (75%).Conclusion: There was a significant correlation between age, education, and income regarding the knowledge around self-medication with a p-value <0.05. There also remained a significant correlation between knowledge, attitude, and practice.